2019
DOI: 10.1111/risa.13283
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions Toward Drinking Water Quality Among Private Well Owners in Ireland: The Illusion of Control

Abstract: In rural areas where no public or group water schemes exist, groundwater is often the only source of drinking water and is extracted by drilling private wells. Typically, private well owners are responsible for the quality and testing of their own drinking water. Previous studies indicate that well owners tend to underestimate the risks of their well water being contaminated, yet little is known about why this is the case. We conducted a qualitative study by interviewing private well owners in Ireland to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 78 publications
4
20
0
Order By: Relevance
“…Emergent themes extended beyond the topic of testing and included other well stewardship behaviors, such as well maintenance and treatment. Participants in this predominantly Latino community reported behavioral factors that are commonly observed in other rural communities, corroborating existing literature on well stewardship [11][12][13][14][15][16]. Additionally, two themes emerged that have not been reported in well stewardship literature: landlords and neighbors and home repair experience.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Emergent themes extended beyond the topic of testing and included other well stewardship behaviors, such as well maintenance and treatment. Participants in this predominantly Latino community reported behavioral factors that are commonly observed in other rural communities, corroborating existing literature on well stewardship [11][12][13][14][15][16]. Additionally, two themes emerged that have not been reported in well stewardship literature: landlords and neighbors and home repair experience.…”
Section: Discussionsupporting
confidence: 81%
“…Literature on the behavioral factors impacting well stewardship is extensive. Research shows that private well users are often satisfied with the quality of their well water and confident that it is safe to drink [11][12][13]. Many note its good taste, smell, and clarity [12,13] and may not see the need for testing and treatment due to low perceived risk of water contamination and related health effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…They also described barriers related to landlords and neighbors, which have not been reported previously. Additionally, participants reported facilitators that have been observed in other communities, including concerns about (perceived risk of) water contamination, knowledge of agricultural sources of contamination, and a responsibility to protect family [13,14]. DIY home repair experience also emerged as a facilitator, which has been previously reported in well stewardship literature.…”
Section: Discussionmentioning
confidence: 72%
“…The responsibility to protect family and DIY home repair experience emerged as notable facilitators within the Spanish focus groups. Previous studies on well water testing have also observed that the obligation to protect vulnerable family members and the belief that testing is useful to protect family facilitates testing behavior [13,14]. Messages around the responsibility to protect family may be particularly resonant among Latino communities as family and a sense of collectivism are commonly noted as critical aspects of Latino culture [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation